Matsushita leadership : - Kotter, John P. (Free Press, 1997)
The Matsushita story expands our notion of the possible, even for a sickly youngster who did not have the benefit of a privileged background, education, good looks, or a charismatic presence. It tells us much about leadership, entrepreneurship, a drive for lifelong learning, and their roots. It demonstrates the power of a longterm outlook, idealistic goals, and humility in the face of great success. Matsushita Leadership is both a biography and a set of lessons for careers and corporations in the 21st century. An inspirational story and a business primer, the implications are powerful, for organizations and for living a meaningful life.